Baudelaire’s “Le Jet d’eau”: Verbal-Visual Inquiry and the Illustrated Book - Eric T. Haskell (Interfaces)
A single text illustrated by several artists presents a unique opportunity for image-text inquiry. This is indeed the case with the illustrators of Baudelaire’s “Le jet d’eau” from his celebrated Fleurs du mal. As each illustrator renders the text into images that represent a unique “reading” of it, our understanding of the poetic gesture is frequently enriched by the graphic gesture. Novel critical points of view which may generate a substantial rethinking of the aesthetic contours of the textual entity thus come into focus. The traditional function of illustration as shedding light onto the word, or of actually extending its meaning to transcend habitual mimetic approaches, evolves with the advent of Modernity as modes of representation espouse fresh contours. “Le jet d’eau” has had a prolific career in the twentieth-century livre d’artiste. Offering a rich terrain of interpretative possibilities, this poem has enticed an array of artists to picture it often unexpected ways. Our point of departure will consider both poetic and graphic universes as écritures whose intersections propose uncommon thresholds beyond which are poised new ideas. This notion is central to our concerns. Similarly, the dynamics of IMAGinING ideas, the interfacing of verbal and visual planes, and the move from representation to abstraction are germane to this investigation. Thus, this discussion of how twentieth-century artists have represented this nineteenth-century text will at once re-frame and re-figure the intrinsic value of illustration as interpretation.